Structural, optical and Judd-Offelt intensity parameters of samarium doped with zinc tellurite glasses - Tafida, R. A.; Halimah, M. K.; Azlan, M. N.; Adamu, S. B.; Lakin, I. I. (Elsevier, 2022)
Objective: The current challenges in materials science and technology is to modify the optical response of rare-earth-doped inorganic glasses for optical applications. The main objectives of the present study are to identify the effect of samarium oxide concentration on the linear optical properties of the zinc tellurite glass system and to use the Judd–Ofelt analysis to study the compositional dependence of the optical properties of the synthesized glasses. Mehodology: Zinc tellurite glasses [(TeO2)0.7 (ZnO) 0.3]1−x [Sm2O3NPs] x, with x = 0.01, 0.02, 0.03, 0.04 and 0.05 molar fraction are prepared by melt quenching technique. The glass samples were produced by employing high-purity analytical chemicals of TeO2 (Alfa Aesar 99.99 per cent), ZnO (Alfa Aesar 99.99 per cent) and Sm2O3 NPs (Alfa Aesar 99.99 per cent). The density of the glass samples was determined based on Archimedes principles with distilled water as an immersed liquid. The density measurement was taken at 10 different times and the average value was recorded. Results: Densimeter, Fourier transform infrared (FTIR) and X-ray diffraction (XRD) were used to study the physical and structural properties. The density and molar volume increases from 5.10 to 5.32 g/cm3 and 27.06–27.54 cm3/mol with an increase in Sm2O3 NPs concentrations. The XRD revealed that the glasses are amorphous. FTIR spectrum reflects the TeO4 structural unit stretching mode. The UV-Vis absorption spectra have seven absorption peaks from the ground state 6H5/2 to 4F7/2, 4I9/2, 6F11/2, 6F9/2, 6F7/2,6F5/2, and 6F3/2 excited energy levels of Sm3+ NPs. The emission spectra under 404 nm wavelength comprised of four bands at 566 nm, 604 nm, 647 nm, and 710 nm represented as transitions. The presence of Sm2O3 NPs was confirmed by high-resolution electron microscopy transmission (HR-TEM) with a particle size of 72.43 nm. Judd-Offelt parameters ( = 4.94, and ) were obtained from the least square fitting and the results revealed that the glasses have potential for laser application.